David Copperfield a BBC-Production Based on the Novel by Charles Dickens - Curtis, Simon; Collins, Andy; Hoskins, Bob; Smith, Maggie; Radcliffe, Daniel (BBC Worldwide, 2001)
The 1999 BBC presentation of David Copperfield demonstrates what can be accomplished with a clear artistic vision and excellent craftsmanship: it is an example of a literary adaptation done right, resulting in a very entertaining program that also happens to be very faithful to the original novel ... One of the most striking things about David Copperfield is how well it captures the tone of Dickens’ novel; no easy feat, since Dickens was both a comedic and a dramatic writer, and in David Copperfield he mixes melodrama with strongly autobiographical material. The cast of David Copperfield fits the bill very nicely, with talented actors who are able to present the characters as slightly larger than life, yet at the same time as real human beings. [www.dvdtalk.com]